(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article is based on an analysis of the principles that the Political Constitution of the United Mexican States (CPEUM) establishes as guidelines for the judicial career, these principles are considered guiding the ethical behavior of all judicial servants. A comparative study is approached between the Code of Ethics of the Judicial Power of Tabasco (CET) with other main positive legislations, of the tools that judicial officials have. Strategies implemented to achieve the consolidation of a true institutional renewal, as well as what are the tools available to each judicial servant that they have to carry out their work. It should be noted that these normative and institutional instruments have been developed and are aimed at generating awareness in all judicial officials at the levels of the administration and administration of justice, not only of those who exercise the function of judge, but also of the server who performs the slightest activity at the service of the judiciary, as well as of the Tabasco society that demands greater credibility and certainty in its actions.